Reference-Based Benefit Design Changes Consumers’ Choices And Employers’ Payments For Ambulatory Surgery - Robinson, James C.; Brown, Timothy; Whaley, Christopher (Health Affairs, 2015)
Some employers are using reference-based benefit (RBB) designs, also known as "reference-based pricing," to encourage patients to select lower-price ambulatory surgery centers instead of expensive hospital outpatient departments. This article analyzes the impact of such benefit designs for cataract removal surgery from the period 2009-13, using data on 2,347 surgical patients covered by the California Public Employees Retirement System (CalPERS), in comparison to 14,867 patients enrolled in non-CalPERS Anthem Blue Cross plans, which are not covered by RBB. After adjusting for changes in patient case-mix and other factors, the shift to RBB was associated with an increase in ambulatory surgery center use by 8.6 percentage points compared to trends among Anthem enrollees. Total employer and employee payments per procedure, after adjusting for changes in case-mix severity and market factors, declined by 19.7 percent compared with Anthem enrollees not subject to RBB. Consumer cost-sharing requirements increased for CalPERS patients who continued to use hospital outpatient departments but who were not exempted from RBB because of geographic or clinical factors. Reference-based benefits for cataract surgery saved CalPERS $1.3 million in the two years after implementation.